Guidance and Training for Banana Farmers in Padang Tiji District to Make Trichoderma Sp from Various Sources - Bukhari, Bukhari; Khalidin; Cut Muliasari (Britain International of Exact Sciences (BIoEx) Journal, 2026)
The income of Padang Tiji farming community has been sufficient to support their families so that some of them send their children to college. But recently, because of the failure of their banana farming business due to Fusarium wilt disease, their lives have become difficult. Therefore, we, the teaching staff of the Faculty of Agriculture, took the initiative to carry out community service to help banana farmers in Meukee Village, Padang Tiji District. The community service is in the form of guidance and training in making Trichoderma Sp from several sources including: Bamboo roots and leaves and from fertile soil that is still original through a number of media, which began by training 5 core workers as pioneers, then with the following stages: (1) Taking Trichoderma Sp mother from various sources, (2) Cultivating it on PDA media to purify, (3) Cultivating again on Corn, rice and husk media and (4) Propagation on Corn and Husk media in a larger capacity so that the result is that each member of the farming group is able to develop their own trichoderma reaching 10 kg of media. This guidance was very successful because more than 80% of the members of the "Makmu Beusare" farmer group have been able to make trichoderma from various sources and media with the best source being a mixture of fertile soil, bamboo roots and leaves, while the best breeding media from a number of media used is rice husks. has been used on their banana plants to prevent Fusarium oxysporium wilt disease.